OPTIMISASI ECONOMIC DISPATCH PADA SISTEM KELISTRIKAN 150 kV BALI MENGGUNAKAN IMPERIALIST COMPETITIVE ALGORITHM - Ayrthon Senapati, I G.N.; Manuaba, Ida Bagus Gede; Hartati, Rukmi Sari (Jurnal SPEKTRUM; Vol 7 No 3 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i03.p8, 2020)
The purpose of the Economic Dispatch is to determine the distribution of each unit in providing the requested load, so that the load demand can be met at the lowest possible cost taking into account the limitations of the generator and available system. Commonly the researcher use some methods to solve economic dispatch, such as Lagrange, Genetic Algorithm (GA), and others optimization methods. Latest Artificial Intelligent technology had invented the solution to solve the optimization problem especially for economic dispatch, its named Imperialist Competitive Algorithm (ICA) which in this project, ICA become the solution to solve economic dispatch problem in Bali 150 kV interconnection system. The simulation result the compared by the result using Lambda Iteration and Particle Swarm Optimization (PSO) method. Simulation result show that the ICA method is able to provide a better solution in Bali 150 kV interconnection system. The difference in generation costs between the Imperialist Competitive Algorithm (ICA) method and the Particle Swarm Optimization (PSO) method is 1685.19 $/h or savings are made at 0.24%. While the difference in generation costs between the Imperialist Competitive Algorithm (ICA) method with the Lambda Iteration method is 7116.45 $/h or savings are made at 1.03%.